Energy cost and energy sources of an elite female soccer player to repeated sprint ability test: A case study - Perroni, F.; Emerenziani, G. P.; Pentenè, F.; Gallotta, M. C.; Guidetti, L.; Baldari, C. (The Open Sports Sciences Journal, 2019)
Background: Intense physical efforts performed at maximal or near-maximal speeds and the ability to recover among sprint are important characteristics of a soccer player. In the last years, women's soccer has become a rapidly and markedly growing sport (+34% of new players from 2000). Objective: The aim of this case study was to analyse the performance (total time -TT; fatigue index percentage -IF%) and physiological (aerobic and anaerobic) responses to Repeated Sprint Ability test (RSAt) of an elite female player. Methods: To identify the contribution of the 3 energy sources at the beginning, middle, and at the end of the different sprint of RSAt performance in a female player (age: 30 years; BMI: 20.3 kg/m2), which requested 7x30 m sprints (25 s active recovery among sprints) with a change of direction, a portable metabolimeter and software dedicated were used. A repeated measure MANOVA over the 7 sprints time series was applied (p< 0.05). Results: Results showed that TT was 58.71 s (Ideal Time: 56.98 s) with IF% of 3.0%. Energy contributions were given for 80.3% by aerobic, 19.2% by anaerobic lactid, and 0.5% by anaerobic alactid sources. We have found different kinetics in the heart rate (HR) and maximum oxygen uptake with the oxygen uptake that reached the peak when HR was still rising. Conclusion: Considering that the energy consumption during intermittent exercises requires different metabolism as a result of physiological stimuli proposed, the present findings substantiate the need to choose specific and adequate training methods for female soccer players that aim at increasing their RSA performances.